Crescimento e rendimento da berinjela sob fontes e doses de nitrogênio - Soares, Alinne Menezes (2016)
Eggplant is a vegetable that responds to nitrogen fertilization, with improvements in their growth and fruit yield. The study was conducted at Federal University of Paraíba, Areia, PB, and aimed to evaluate sources and doses of nitrogen on the growth and production of eggplant in a randomized complete block in a factorial 5 x 2, with three replications, with five N rates (0; 60; 120; 180; 240 kg ha-1) and two sources (urea and ammonium sulfate). Were evaluated: SPAD index, plant height, dry weight of shoot, leaf area, leaf area index, leaf area ratio, specific leaf area, leaf weight ratio, length and diameter of fruits, number and production of commercial fruits plant-1, average weight of commercial fruits, total and commercial fruit yield and contents of N, P and K leaf. Nitrogen improved all characteristics evaluated, except foliar K content, but there were differences in their sources. The plant height, shoot dry weight, leaf area and leaf area index increased with the evaluation periods in the two sources, and a reduction in the SPAD index and leaf weight ratio. The length of fruits increased only with nitrogen, but the number and fruit yield plant-1, diameter and average fruit weight were higher in ammonium sulfate. Total and commercial yield reached the maximum of 66 and 57 t ha-1 and 60 and 52 t ha-1, respectively, with the use of nitrogen in the form of ammonium sulfate and urea. Foliar N content was influenced by nitrogen and phosphorus content by ammonium sulfate.